Left atrial size quantification using non-contrast-enhanced cardiac computed tomography – association with cardiovascular risk factors and gender-specific distribution in the general population: the Heinz Nixdorf Recall study. (October 2014) - Mahabadi, Amir A; Lehmann, Nils; Sonneck, Nina C; Kälsch, Hagen; Bauer, Marcus; Kara, Kaffer; Geisel, Marie H; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Möhlenkamp, Stefan
Background: Left atrial (LA) size is associated with cardiovascular mortality and morbidity. Once cardiac computed tomography (CT) is performed, information on LA size is readily available without additional contrast media or radiation exposure. Purpose: To determine the association of CT-derived LA area and body surface area-adjusted (BSA) LA index with cardiovascular risk factors and describe age- and gender-specific normative values in a general population cohort. Material and Methods: This study included 3945 participants (mean age, 59 ± 8 years; 53% women) from the community-based Heinz Nixdorf Recall Study. LA area in an axial image at the level of the mitral valve was quantified from non-contrast-enhanced electron-beam CT by manual delineations of the boundaries of the LA with exclusion of subjects with prevalent cardiovascular disease. Definition of normative values was performed in subjects without predictors of LA enlargement. Results: LA quantification was feasible in all subjects. Men had larger LA size (1856 mm 2 vs. 1677 mm 2, P  < 0.0001), while after adjustment for BSA, this effect was inverted (910 mm 2 /m 2 vs. 933 mm 2 /m 2 for men and women, P  < 0.0001). Determinants of body size were major predictors of LA size (body mass index [BMI]: R 2  = 0.195, BSA: R 2  = 0.216, both P  < 0.0001). Blood pressure was associated with LA size (parameter-estimate [95% confidence interval] = 51.0 (4.9–57.1) mm 2 /10 mmHg for systolic, 31.4 (25.4–37.4) mm 2 /5 mmHg for diastolic blood pressure, 214.6 (186.9–242.3) mm 2 for antihypertensive medication, P  < 0.0001 for all). Cholesterol levels, lipid-lowering therapy, and diabetes were associated with LA in univariable analysis, however, correlations were low (r 2  ≤ 0.026). Current smoking was associated with reduced LA size (–115.9 [–149.0 – –82.8] mm 2, P  < 0.0001). In multivariable regression, BMI, blood pressure, antihypertensive medication, and smoking remained associated with LA size ( P  < 0.005). Conclusion: Non-contrast-enhanced cardiac CT enables LA quantification with body size, hypertension, and smoking status being predictors of LA size.